Peranan Orang Tua dan Ninik Mamak Sebelum Perkawinan di Nagari Sibarambang dalam Perspektif Hukum Islam - Daharis, Ade; Putra, Deri (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The research background is that parents and Ninik Mamak Ampek Jinih in Nagari Sibarambang in Nagari Sibarmabang, where parents and Ninik Mamak play a role in managing the administration of the marriage of the prospective bride and groom who want to get married where in managing the administration of marriage. This type of research is field research using qualitative research methods. The research was conducted in Nagari Sibarambang, X Koto Diatas District, Solok Regency. Primary data sources are parents who are going to marry off their children, the bride and groom, and Ninik Mamak Ampek Jinih in Nagari Sibarambang. Data collection techniques are observation, interviews, and documentation. The results of the study show that (1) The role of parents and Ninik Mamak before the wedding in Nagari Sibarambang is not only a mere witness but has a very important role from the administration of marriage to walimah of marriage, and in terms of the conditions that may become guardians of marriage are parents and Ninik Mamak as witnesses wedding. The law of marriage carried out by married couples in Nagari Sibarambang can be classified into 3, namely obligatory, sunnah and mubah.